2010
DOI: 10.1086/655778
|View full text |Cite
|
Sign up to set email alerts
|

Striking at the Roots of Crime: The Impact of Welfare Spending on Crime during the Great Depression

Abstract: During the Great Depression contemporaries worried that people hit by hard times would resort to crime. President Franklin Roosevelt argued that the massive government relief efforts “struck at the roots of crime” by providing subsistence income to needy families. After constructing a panel data set for 81 large American cities for the years 1930–40, we estimate the effect of relief spending by all levels of government on crime rates. The analysis suggests that a 10 percent increase in relief spending during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 50 publications
(26 reference statements)
0
18
0
1
Order By: Relevance
“…Fishback, Johnson and Kantor (2010), studying a panel of 83 cities between 1930 and 1940, found that New Deal relief decreased property crime during the Great Depression. Zhang (1997) examined states in 1987 and found a negative association between state AFDC generosity and property crime.…”
Section: Effects Of Welfare On Crimementioning
confidence: 99%
“…Fishback, Johnson and Kantor (2010), studying a panel of 83 cities between 1930 and 1940, found that New Deal relief decreased property crime during the Great Depression. Zhang (1997) examined states in 1987 and found a negative association between state AFDC generosity and property crime.…”
Section: Effects Of Welfare On Crimementioning
confidence: 99%
“… See, for example, Levitt (), Kessler and Levitt (), Di Tella and Schargrodsky (), Klick and Tabarrok (), Ayres and Levitt (), Freeman (), Grogger (), Machin and Meghir (), Fishback, Johnson, and Kantor (), Gould, Weinberg, and Mustard (), Shavell (), and Marvell and Moody (). …”
mentioning
confidence: 99%
“…Foley examined the temporal patterns of crime in twelve American cities to show that "welfare beneficiaries consume welfare-related income quickly and then attempt to supplement it with criminal income" (2011, p. 97). Fishback et al (2010) found that, during the Great Depression, cities with higher levels of relief spending saw significantly lower levels of crime. There is also evidence that non-receipt of welfare 2 increases women's risk of offending (Monte andLewis 2011, Thompson andUggen 2013).…”
Section: The Political Economy Of Crimementioning
confidence: 99%